2021
DOI: 10.21608/sjdfs.2021.195585
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Phytochemical Composition of Sargassum Vulgare at Hurghada Red Sea Coast - Egypt

Abstract: Macroalgae produce a wide variety of chemically active secondary metabolites. Brown seaweed; Sargassum vulgare and its associated seaweeds were collected from Hurghada Red sea coast of Egypt. Optimal physicochemical properties; slightly alkaline; low turbidity, moderate temperature and available nutrient content of saline water produced massive growth of S. vulgare (53% covering percentage) during autumn (2018). Heavy metals accumulation inside the investigated seaweed S. vulgare was within the usually range. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…This may be due to the specific compounds in algae (El Modafar et al., 2012; Ammar et al., 2017; Ali et al., 2021), fungi (Sobolev, 2013; Aisyah et al., 2015) or bioprocessed elicitors (Ramakrishna et al., 2017). Metabolite profiling of Sargassum vulgare revealed several bioactive molecules, including multiple acids such as ascorbic acid, gallic acid, palmitic acid and oleic acid (Mahmoud et al., 2019; Abu Ahmed et al., 2021). These acids can subsequently loosen the cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the specific compounds in algae (El Modafar et al., 2012; Ammar et al., 2017; Ali et al., 2021), fungi (Sobolev, 2013; Aisyah et al., 2015) or bioprocessed elicitors (Ramakrishna et al., 2017). Metabolite profiling of Sargassum vulgare revealed several bioactive molecules, including multiple acids such as ascorbic acid, gallic acid, palmitic acid and oleic acid (Mahmoud et al., 2019; Abu Ahmed et al., 2021). These acids can subsequently loosen the cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…All compounds had antioxidant, antimicrobial, Anti fungi, antiviruses, Antiulcer, anti-inflammatory, and anticancer (Table 5). In similar study of Sudha and Balasundaram, a total of twenty bioactive chemicals have been reported from ethanolic extract of P. pavoica by (GC-MS) analysis [54] In another study of Usha and Rani GC-MS analysis revealed eighteen components in the methanol extract of P. pavonica [67].…”
Section: Gc-ms Analysis Of Algal Extractsmentioning
confidence: 91%
“…Our results are in agreement with Do et al , who used ethanol (75%) and acetone (75%) to measure total phenolic and total flavonoid. It was concluded that acetone gave a total flavonoid result (0.64) more than ethanol (0.35), but ethanol showed atotal phenolic (1.36) more than acetone (0.87) [53][54].The lowest total carotenoids (0.183), phenolics (0.9), tannins (0.0162), flavonoids (1.875) and sulfated polysaccharides (0.0415) were observed in the EtOAc extract of p. pavonica (Figure 2). The DPPH radical scavenging assay is widely used as a prescreening tool for novel antioxidants derived from natural sources due to its reproducibility and stability [36].…”
Section: 2quantitative Analysis Of Phytochemical Substances and Antio...mentioning
confidence: 99%
“…Several phytoconstituents in D. simplex ChlE were qualitatively screened using previously published chemical analyses [31,32]. The results are tabulated in Table 1.…”
Section: Phytochemical Screeningmentioning
confidence: 99%